THE STUDY OF THE ASSOCIATIONS OF BLOOD LIPID PROFILE WITH THE EXPRESSION OF ATHEROSCKLEROSIS AND STRUCTURAL CHANGES IN THE ACHILLES TENDON - A. V. Anikina; M. E. Amelin; Yu. P. Nikitin (Атеросклероз, 2018)
Objective. To study the possible relationship between the level of different cholesterol fractions and the severity of atherosclerosis with the change in the Achilles tendon. Material and methods. A random selective group of patients of the vascular neurosurgery department of the Federal Center of Neurosurgery of the Ministry of Health of the Russian Federation (Novosibirsk) was examined for monolateral or bilateral atherosclerosis of the carotid arteries with varying degrees of stenosis. Our study included 25 people aged 42-65 years. All patients underwent a series of clinical and instrumental studies (ECG, computed tomography, angiography, collection of clinical data, biochemical studies of blood serum). Results. In the group with a high content of low cholesterol and low-density lipoprotein cholesterol, a direct correlation was observed between cholesterol level and severity of atherosclerosis with the size and density of the Achilles tendons. Conclusions. An increased level of blood cholesterol concentration, especially in individuals with carotid stenosis, may be involved in the processes of connective tissue degeneration. With an increase in the level of total cholesterol above 5 mmol / l, an increase in the volume of the Achilles tendon and an increase in its density is noted.